Remittances and the future of African economies - Ibrahim A. Adekunle; Sheriffdeen A. Tella (African Governance and Development Institute (AGDI), 2021)
African nations have in time, passed over-relied on remittances inflow to augment domestic finances needed for growth. Despite the volume and magnitude of remittances that have to serve as an alternative source of investment financing, African remains mostly underdeveloped. The altruistic motives of sending remittances to Africa are likely to fade with time. In this study, we argued that the altruistic connection that has been the bedrock of sending money to African countries would eventually fade when the older generation passes away. To lean empirical credence to this assertion, we examine the structural linkages and the channels through which remittances predicts variations in financial developmentas a threshold for gauging the future of African economies. We gathered panel data on indices of remittances and financial development for thirty (30) African countries from 2003 through 2017. We employed the dynamic panel system generalised method of moment (dynamic system GMM) estimation procedure to establish a baseline level relationship between the variables of interest. We adjusted for heterogeneity assumptions inherent in ordinary panel estimation and found a basis for the strict orthogonal relationship among the variables. Findings revealed that a percentage increase in remittances inflow has a short-run, positive relationship with financial development in Africa. The result further revealed that the exchange rate negatively influences financial development in Africa. Based on the findings, it is suggested that, while attracting migrants' transfers which can have significant short-run poverty-alleviating advantages, in the long run, it might be more beneficial for African governments to foster financial sector development using alternative financial development strategies in anticipation of a flow of remittance that will eventually dry up.
Keywords: F37; G21; O16; 330; Remittance; Financial Development; African Economies; System GMM; Africa